Efektivitas Penggunaan Media Canva dalam Membuat Poster pada Siswa Kelas VIII MTS Yapit Taretta - Haeril Herisal; Hambali Hambali; Akbar Avicenna (Lembag, 2024)
The effectiveness of using canva media in creating learning posters at MTs Yapit Taretta is creating learning media that utilizes or uses the Canva application as a design tool. This use is an effort to motivate students at MTS to learn. The aim of this research is to determine the effectiveness of using Canva media in making posters for MTs Yapit Taretta students. This research is field research with a qualitative approach, with data collection: (1) Observation Technique, to obtain an overview of the effectiveness of using Canva media, (2) Interview Technique, used to obtain data regarding the effectiveness of using Canva media in making posters for MTs Yapit Taretta students , (3) Documentation technique, used to collect information in the form of documents or school archives regarding the effectiveness of using Canva media in making posters for MTs Yapit Taretta students. The data analysis used is data reduction, data display, data withdrawal, and data validity testing. The results of the research show that the effectiveness of using the Canva application as a learning medium is going well. The effectiveness of the Canva application is used to create learning media in the form of learning posters. Through its success, the Canva application has become the right design tool to help teachers and students create interesting learning media, increase creativity, make it easier for students to understand the material, is easy to access, and many elements and features are free.